Critical Analysis Of The Evolving Role Of Dentistry In Preventive And Restorative Medicine - Asiri, Abdullah Mohammed Saeed; Alhamoud, Saeed Mohammed; Alayoubi, Wael Adnan; Alshahrani, Omar Ali Mohammed; Alhendi, Rana Jameel; Al-Hejin, Abdulsalam Mahmoud; Jar, Alabbas Abdulghani; Fedah, Ibrahim Mohammed (Journal of Ecohumanism, 2024)
Dentistry has kept up with this trend towards preventive and restorative health care in the patient practice pattern. In the past, dentistry primarily concentrated on simple problems like filling in cavities and pulling out of teeth, it is today a health science of immense value. In recent years, preventive oral health care intervention, which aims to identify latent oral pathoses and elevate community health oral hygiene standards, is increasingly appreciated for suppressing systemic diseases, including cardiovascular illnesses, diabetes, and respiratory ailments. In addition, restorative dentistry has developed a new material, techniques, and technology that enhance the quality of life for patients with dentistry disability. This review looks at dentistry's current and future trends in health promotion and restoration capacity, with special reference to health systems. This article discusses the evolution of dental practices, how dentistry interfaces with other branches of medicine, and some of the issues that have affected this field. Further, it throws light on the new advancements in dental technology, patient care diplomacy, and novel concepts of healthcare delivery systems.